RGS proteins in heart: brakes on the vagus - Stewart, Adele; Huang, Jie; Fisher, Rory A. (Frontiers in Physiology, 2012)
It has been nearly a century since Otto Loewi discovered that acetylcholine (ACh) release from the vagus produces bradycardia and reduced cardiac contractility. It is now known that parasympathetic control of the heart is mediated by ACh stimulation of Gi/o-coupled muscarinic M2 receptors, which directly activate G protein-coupled inwardly rectifying potassium (GIRK) channels via Gβγ resulting in membrane hyperpolarization and inhibition of action potential (AP) firing. However, expression of M2R–GIRK signaling components in heterologous systems failed to recapitulate native channel gating kinetics. The missing link was identified with the discovery of regulator of G protein signaling (RGS) proteins, which act as GTPase-activating proteins to accelerate the intrinsic GTPase activity of Gα resulting in termination of Gα- and Gβγ-mediated signaling to downstream effectors. Studies in mice expressing an RGS-insensitive Gαi2 mutant (G184S) implicated endogenous RGS proteins as key regulators of parasympathetic signaling in heart. Recently, two RGS proteins have been identified as critical regulators of M2R signaling in heart. RGS6 exhibits a uniquely robust expression in heart, especially in sinoatrial (SAN) and atrioventricular nodal regions. Mice lacking RGS6 exhibit increased bradycardia and inhibition of SAN AP firing in response to CCh as well as a loss of rapid activation and deactivation kinetics and current desensitization for ACh-induced GIRK current (IKACh). Similar findings were observed in mice lacking RGS4. Thus, dysregulation in RGS protein expression or function may contribute to pathologies involving aberrant electrical activity in cardiac pacemaker cells. Moreover, RGS6 expression was found to be up-regulated in heart under certain pathological conditions, including doxorubicin treatment, which is known to cause life-threatening cardiotoxicity and atrial fibrillation in cancer patients. On the other hand, increased vagal tone may be cardioprotective in heart failure where acetylcholinesterase inhibitors and vagal stimulation have been proposed as potential therapeutics. Together, these studies identify RGS proteins, especially RGS6, as new therapeutic targets for diseases such as sick sinus syndrome or other maladies involving abnormal autonomic control of the heart.